Patient satisfaction and associated factor at red cross pharmacies in Addis Ababa, Ethiopia - Fikreselam Habte; Melak Gedamu; Chalelgn Kassaw (BMC, 2023)
Abstract Background Patient satisfaction is a crucial aspect of healthcare, reflecting the positive feelings patients experience when using a service. It serves as an indicator of the gap between expected and actual service quality from the patient's perspective. Measuring patient satisfaction is recommended for healthcare providers at all levels as it contributes to improvement efforts. In recent times, pharmacy services have evolved beyond merely supplying medications to becoming more patient-centered and caring. Given the high number of patients relying on the limited Red Cross community pharmacies in the city, this study aims to assess patient satisfaction and identify factors associated with patient satisfaction towards Red Cross Pharmacies in Addis Ababa, Ethiopia. Patients and methods Cross sectional study design was conducted from August 15 to August 30, 2022 in three Red Cross Pharmacies in Addis Ababa. Patients were selected by Convenience sampling technique. Structured questionnaire was used to assess patient satisfaction. Bivariate and Multivariate logistic regression were computed to assess statistical association between the outcome variable, and independent variables. SPSS version 21 was used for analysis. Results Four hundred seven participants were willing and completed the study. The overall satisfaction towards Red Cross pharmacy service was 60.4%. Inadequate counselling was main reason for dissatisfaction (45%). Regarding associated factors, unavailability of some medications (Adjusted odds ratio = 0.393, 95% CI: 0.208-0.741), unfair medication cost (Adjusted odds ratio = 0.613, 95% CI: 0.607-0.910), and lack of organized pharmacy work flow (Adjusted odds ratio = 0.105, 95% CI: 0.049-0.221) were negatively associated with clients' satisfaction. Conclusion This study provides significant insights into patient satisfaction with Red Cross pharmacy services in Addis Ababa, Ethiopia, revealing an overall patient satisfaction rate of 60.4%. While a substantial number of patients had positive experiences, dissatisfaction due to inadequate counseling was a notable concern. Factors negatively associated with patient satisfaction, including medication unavailability, unfair cost, and a lack of organized workflow, further highlight the need for targeted interventions to improve patient experiences. Addressing these issues will be critical to enhance pharmaceutical care services and bridge the gap between patient needs and satisfaction.